Exploration of digital filters on cardiac monitor devices equipped with non-invasive blood pressure (NIBP) - Nugraha, Priyambada C.; Sumber, Sumber; Muzachim, Zuva; Rabani, Rifqi; Alhaq, Elmira Rofida; Triwiyanto, Triwiyanto; Abdullayev, Vugar (Indonesian Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2024)
Heart disease is a leading cause of global mortality, making accurate monitoring essential for early detection and prevention of complications. Although heart monitoring technology has advanced, there are still limitations in precisely detecting early symptoms. This study aims to develop a Cardiac Monitor device capable of monitoring patients with heart conditions through three main parameters: electrocardiogram (ECG), phonocardiogram (PCG), and non-invasive blood pressure measurement (NIBP). The system designed in this research integrates digital filters, namely Butterworth (order 2, 4, 8) and Kalman, to enhance the quality of ECG and PCG signals. Additionally, the oscillometric method in non-invasive blood pressure measurement (NIBP) is used as a comparison for blood pressure estimation by analyzing the correlation between the R peak on the ECG signal, pulse transit time (PTT), and the first and second heart sounds (S1, S2) on the PCG signal. Blood pressure estimation is performed using algorithmic calculations to determine the accuracy of the design module in measuring systolic and diastolic pressure. The results indicate that the 8th-order Butterworth filter is more effective in reducing noise in ECG and PCG signals compared to the Kalman filter. The study also finds a significant correlation between the R peak on the ECG and the first heart sound on the PCG. The design module’s blood pressure measurement errors compared to algorithmic estimates are 4.54 ± 4.94 mmHg for systolic pressure and 6.57 ± 3.83 mmHg for diastolic pressure, which are close to the AAMI standard of 5 ± 8 mmHg. These findings highlight the great potential of the developed Cardiac Monitor device in improving early diagnosis accuracy and heart disease management.